Perancangan UI/UX Layanan Servis Kendaraan On-Demand Berbasis Human-Centered Design - Andhika Satya Aryaguna; Diena Noviarini; Adnan Kasofi (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This research is motivated by the high financial information asymmetry (price manipulation practices) and spatial panic experienced by users when facing automotive emergencies on the road. The objective of this study is to design a user interface prototype for an on-demand vehicle service application that provides absolute price transparency and accelerates access to mechanical assistance. This study employs a Human-Centered Design (HCD) approach through the Design Thinking methodology, consisting of empathize, define, ideate, prototype, and test stages. The designed solution focuses on the Fixed-Price Checkout feature to lock in cost details, as well as the integration of One-Tap SOS and satellite Live Tracking to mitigate geographic disorientation. Functionality testing was conducted through Blackbox Testing, while the usability level was evaluated using the System Usability Scale (SUS) instrument involving 30 respondents. The Blackbox testing results showed a 100% functional precision rate. The SUS evaluation resulted in an average score of 83.67, which falls into the Excellent category with a B+ Grade (Acceptable). Furthermore, qualitative data analysis and pre-test and post-test comparisons demonstrated a significant decrease in anxiety levels and an increase in user trust. In conclusion, the Human-Centered Design-based on-demand vehicle service interface design has proven to be effective, solution-oriented, and user-friendly in resolving information asymmetry issues in the automotive aftersales sector.